1981
DOI: 10.1111/j.1471-4159.1981.tb01664.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Modulation by Avermectin B1a of the GABA/Benzodiazepine Receptor Complex of Rat Cerebellum

Abstract: Avermectin B1a, a macrocyclic lactone anthelmintic agent, causes a concentration-dependent increase of [3H]flunitrazepam binding to membranes from rat cerebellum by increasing the affinity and the number of binding sites. This effect appears to be independent of the concentration of chloride ions. The effects of avermectin B1a occur with high affinity (EC50 = 70 nM), and they persist after washing of the membranes with drug-free buffer. Pretreatment of the membranes with Triton X-100 completely abolishes the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…In this study, tail contractions were absent but no gross morphological defects were observed among embryos exposed to abamectin insecticide from 5–25 hpf. This absence of movement is consistent with other studies showing abamectin neurotoxicity being linked to it agonizing GABA receptors that stimulates release of GABA neurotransmitter and produces paralytic responses 207209 .…”
Section: Behavioral Testing In Zebrafishsupporting
confidence: 92%
“…In this study, tail contractions were absent but no gross morphological defects were observed among embryos exposed to abamectin insecticide from 5–25 hpf. This absence of movement is consistent with other studies showing abamectin neurotoxicity being linked to it agonizing GABA receptors that stimulates release of GABA neurotransmitter and produces paralytic responses 207209 .…”
Section: Behavioral Testing In Zebrafishsupporting
confidence: 92%
“…Like GABA, AVM protected BZ receptor binding sites from heat inactivation, whereas barbiturates and pyrazolopyridines were ineffective . AVM enhancement of BZ binding was additive with that of GABA agonists, and diminished by high concentrations of pyrazolopyridines and some GABA "partial" agonists (Supavilai and Karobath, 1981~;Williams and Risley, 1984).…”
Section: Avm Is a Glycosidic Macrocyclic Lactone Frommentioning
confidence: 93%
“…AVM enhancement (EC,, -30 nM) of BZ binding (both KD and B,,,) has been observed by numerous groups (Williams and Yarbrough, 1979;Paul et al, 1980;Supavilai and Karobath, 1981~;. AVM enhancement was reported in one study to be unaffected by bicuculline methiodide (10 pLIM) (Supavilai and Karobath, 1981~) but others found a partial block by higher concentrations of bicuculline (50-100 pn/r) but not strychnine or picrotoxin (100 pM) (Paul et al, 1980).…”
Section: Avm Is a Glycosidic Macrocyclic Lactone Frommentioning
confidence: 93%
See 1 more Smart Citation
“…Avermectin binds specifically to brain membranes, and enhances GABA binding (Wang & Pong, 1982). Supavilai & Karobath (1981) have also suggested that avermectin enhances benzodiazepine binding to a novel modulatory site on the GABA-benzodiazepine receptor/complex. Whether these effects are correlated with the slow agonist actions of this compound is not yet known.…”
Section: Halothane Ketamine and Diazepammentioning
confidence: 99%